1989
DOI: 10.1007/bf01313750
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a feline T-lymphoblastoid cell line highly sensitive for replication of feline immunodeficiency virus

Abstract: Interleukin-2 dependent feline T-lymphoblastoid cells designated as MYA-1 cells were established. The cells were free from exogenous retroviruses and sensitive for replication of feline immunodeficiency virus (FIV). FIV can grow more efficiently in MYA-1 cells than in feline primary peripheral blood mononuclear cells. This line of cells will be useful not only for isolation and propagation of FIV, but also for further investigation of properties of FIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 8 publications
0
78
0
Order By: Relevance
“…The Petaluma isolate grew well even in CD4-and CD8-negative CrFK cells, and cells persistently infected with this isolate were also established (Yamamoto et al, 1988). However, the Japanese isolates classified as subtype B, FIV/TM-1 and TM-2, did not grow in CrFK cells (Miyazawa et al, 1989). It has also been reported that some viruses isolated in lymphoblastoid cells could be adapted to grow in CrFK cells only after several passages in the lymphoblastoid cell line (Baldinotti et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The Petaluma isolate grew well even in CD4-and CD8-negative CrFK cells, and cells persistently infected with this isolate were also established (Yamamoto et al, 1988). However, the Japanese isolates classified as subtype B, FIV/TM-1 and TM-2, did not grow in CrFK cells (Miyazawa et al, 1989). It has also been reported that some viruses isolated in lymphoblastoid cells could be adapted to grow in CrFK cells only after several passages in the lymphoblastoid cell line (Baldinotti et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Antigens were prepared from viral cultures of domestic cat FIV (FIV-B2546), puma lentivirus (PLV-1695), and lion lentivirus (LLV-438). Stocks were grown in domestic cat origin cell line Mya-1 (Miyazawa et al, 1989), and viral proteins were isolated as previously described (VandeWoude et al, 1997b;TerWee et al, 2005). Reverse-transcriptase positive tissue culture supernatant was centrifuged at 200 3 G (GPR centrifuge, Beckman Instruments, Inc., Fullerton, California, USA) for 10 min at 5 C to remove cellular material.…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…To allow accurate estimation of the proviral load per 10 6 mononuclear cells, a further Taqman PCR designed to measure total sample DNA was performed using primers and probe speci®c for the rRNA gene (Klein et al, 2000). Standards for this PCR were derived from MYA-1 (Miyazawa et al, 1989) genomic DNA. The DNA was quanti®ed by measuring the absorbance at OD 260 and a dilution series was prepared in PCR grade water as before.…”
Section: Determination Of Fiv Proviral Loadmentioning
confidence: 99%